Climate change and fiscal balance in China over the past two millennia. (December 2014) - Wei, Zhudeng; Fang, Xiuqi; Su, Yun
The relation between climate change and historical rhythms has long been discussed; however, this type of study still faces the lack of high-resolution data of long-term socio-economic processes. In this study, we collected 1101 items of direct and proffered evidence from 24 Chinese fiscal and economic history books written by leading contemporary scholars. By analysing the semantics of words, we reconstructed a 2130-year-long fiscal sequence with decadal resolution to express the phase transition of fiscal soundness for approximately 21 dynasties in China. Our reconstruction shows four relatively sufficient stages and three relatively deficient stages, with several secondary stages lasting 60 or 160 years on average within each large stage, from 220bc toad 1910. Then, the fiscal association with climate change was analysed. The results show that the fiscal crisis was more likely to occur in cold-dry climatic scenarios. Both temperature and precipitation displayed more significant effects on the fiscal fluctuation within the long term, particularly for temperature. In short, fiscal decline had a 10-year lag in response to decreasing precipitation, whereas influence of decreasing temperature on the fiscal balance might be through amplifying already deteriorating fiscal conditions. Regional differences existed in the influence of precipitation on the fiscal balance. The precipitation in the Northern China Plain and in the Jiang-Huai area had more significant effects on the fluctuation of the dynastic fiscal balance than on that in the Jiang-Nan area. In particular, the dynastic finance was more sensitive to the change in the precipitation in the Northern China Plain because of its special geographical, economic and social backgrounds.